Pengaruh Self-Regulated Learning, Self-Efficacy dan Perhatian Orangtua Terhadap Prestasi Belajar Matematika Siswa - Sugiyana Sugiyana (Universitas Ahmad Dahlan, 2015)
The purpose of this study was to determine the effect of self regulated learning, self efficacy and parents Â attention to learning achievement in mathematics in class VIII. This study took place in SMPN 1 Gunung Purwosari. Number of samples 89 and take the entire eighth grade students as subjects. Methods of data collection using a scale of self regulated learning, self-efficacy scale, and scale attention parents. Mathematics learning achievement data obtained from the documents in the first semester report cards while collecting data in the second semester. Data analysis technique used is multiple regression analysis. 0,05).